Incentive mechanism design for mandatory green certificate trading in China: A collective action perspective - Ying, Zhou; Xuefeng, Jia; Hui, Wang; Junling, Huang (Energy (Oxford), 2025)
Renewable Portfolio Standards (RPS) system is a mandatory institutional change for China to achieve low-carbon energy transition, its implementation will trigger collective action by market participants. At present, there are market anomalies in the voluntary green certificate trading market in China, such as having no market and low liquidity. Implementing mandatory green certificate trading and designing reasonable incentive mechanisms can effectively solve the collective action dilemma caused by free-riding behavior. Based on the system dynamics model of collective action evolutionary game of market participants, this paper analyzes the incentive effect of relevant institutional parameters of RPS on collective action. The results show that institutional parameters such as quota, penalty, issuance cost coefficient and benchmark price are the key incentive mechanisms affecting the evolutionary equilibrium results of collective action. Specifically, the higher penalty can increase the proportion of quota subjects participating in collective action and play a good incentive role. Lower issuance cost coefficient and benchmark price can encourage green power manufacturers to participate in collective action and improve TGC market liquidity. Quota has no significant incentive effect on the collective action of market participants. Therefore, the scientific design of incentive mechanisms for collective action will effectively promote China's RPS system. The highlights are as follows:●Free-riding behavior is the main reason leading to the failure of green certificate trading in China●Introducing collective action theory into the study of China's quota system●The incentive mechanism of China's compulsory green certificate trading is designed●Higher penalty can effectively stimulate the collective action of quota subjects●The lower issuance cost coefficient and benchmark price stimulates the collective action of green power plants